Marine Renewable Energy Resources in Peru: A Sustainable Blue Energy for Explore and Develop - Cacciuttolo, Carlos (2025)
The Peruvian coast covers more than 3000 km along the Pacific Ocean, being one of the richest seas in terms of biodiversity, productivity, fishing, and renewable energy potential. Marine renewable energy (MRE) in both offshore and coastal environments of Peru is, currently, a huge reserve of practically unused renewable energy, with inexhaustible potential. In this context, renewable energies from hydroelectric, biomass, wind, and solar sources have been applied in the country, but geothermal, waves, tidal currents, and tidal range sources are currently underdeveloped. This article presents the enormous source of sustainable blue energy for generating electrical energy that exists in Peru from waves and tidal resource potential. In addition, this article presents the main opportunities, gaps, and key issues for the implementation of marine renewable energy (MRE), with emphasis on: (i) showing the available potential in the northern, central, and southern Pacific Ocean territories of Peru, (ii) characterizing the marine energy best available technologies to implement, (iii) the environmental and socio-economic impacts of marine renewable energy, and (iv) discussion of challenges, opportunities, and future directions for developments in the marine energy sector. Finally, the article concludes that the greatest possibilities for exploiting the abundant marine renewable energy (MRE) resource in Peru are large spaces in both offshore and coastal environments on the Pacific Ocean that can be considered for harvesting energy. These issues will depend strongly on the implementation of regulations and policies for the strategic use for planning of marine resources, encouraging research and development (R&D) for creating sustainable innovations, incentives for project finance mechanisms, and developing specialized local human capital, considering the sustainability of livelihoods of coastal communities and ecosystems.